Journey of Finding Myself (Comparative & International Education Series, 2022)
I am an ITA. What is that? It is short for International Teaching Assistant – a group of courageous and competent international students who teach or assist in U.S. college classrooms. Being international students, we must navigate an entirely new education system in an unfamiliar language on our own. Being an ITA is even more challenging because we need to be knowledgeable about the subject we teach and have a strong and determined heart. When I first received the assistantship while attending my master’s program, I genuinely felt proud to be recognized as an international student without knowing the hurdles in front of me. I positively thought that speaking good English and being hardworking would make me a cool and competent teacher. However, things did not go as expected. After starting to teach, I experienced tremendous cultural shock and misunderstandings between my students and me. I was entirely lost and started to experience an identity crisis. Fortunately, I found myself in the end.